2009
DOI: 10.1039/b903249e
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the discrimination and classification of prostate cancer cell lines by FTIR microspectroscopy

Abstract: In this study we obtained Fourier transform infrared (FTIR) spectra of fixed prostate cell lines of differing types as well as the primary epithelial cells from benign prostatic hyperplasia (BPH). Results showed that by using multivariate chemometric analysis it was possible to discriminate and classify these cell lines, which gave rise to sensitivity and specificity values of >94% and >98%, respectively. Following on from these results the possible influences of different factors on the discrimination and cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(80 citation statements)
references
References 45 publications
(49 reference statements)
2
75
1
Order By: Relevance
“…This was thought to be due to the nucleus to cytoplasm ratio of the cells being more discriminatory than biochemical changes. However, a recent study 28 has shown that the major reason for discrimination of prostate cancer cell lines, albeit ones from different anatomical positions, by FTIR is the biochemical differences between the cell lines. Thus we can be confident that we are observing discriminatory biochemical differences between the RWPE family of cell lines but it should be stressed that these differences appear to derive from the method of transformation rather than the degree of invasiveness.…”
Section: Laboratory Based and Synchrotron Based Microspectroscopic Studymentioning
confidence: 99%
“…This was thought to be due to the nucleus to cytoplasm ratio of the cells being more discriminatory than biochemical changes. However, a recent study 28 has shown that the major reason for discrimination of prostate cancer cell lines, albeit ones from different anatomical positions, by FTIR is the biochemical differences between the cell lines. Thus we can be confident that we are observing discriminatory biochemical differences between the RWPE family of cell lines but it should be stressed that these differences appear to derive from the method of transformation rather than the degree of invasiveness.…”
Section: Laboratory Based and Synchrotron Based Microspectroscopic Studymentioning
confidence: 99%
“…In order to avoid over-¯tting of the data, as a thumb rule, total number of factors selected for analysis were less than half the number of the spectra in the smallest group. [40][41][42] During PC-LDA, use of less than 10 PC factors for LDA is the best compromise on the information being included and data noise being excluded. 43 During PC-LDA, several factors were explored for classi¯cation and only factors with minimum over-¯tting and maximum classi¯-cation e±ciency were¯nally selected for analysis.…”
Section: Spectral Pre-processing and Data Analysismentioning
confidence: 99%
“…3, a dose-dependent decrease in cell viability was observed with approximate 100% cell death at 20 mM. Inhibitory concentration 50 (IC 50 ) i.e., the concentration required to kill half the population of cells was observed to be approximately 8 mM. A famous axiom in toxicology by Paracelsus states, \The dose makes the poison".…”
Section: Results and Discussion 31 Ptx A®ects Cellular Viability Anmentioning
confidence: 99%